Preparation Optimization and Antioxidant Properties of the β-Glucan and Ferulic Acid/Quercetin Complex from Highland Barley (Hordeum vulgare var. nudum) - Yuanhang Ren; Yanting Yang; Mi Jiang; Wentao Gu; Yanan Cao; Liang Zou; Lianxin Peng (Foods)
Polysaccharides and phenols are commonly co-localized in various plant-derived foods, including highland barley (Hordeum vulgare L. var. nudum Hook. f.). The interactions between these compounds can influence multiple characteristics of food products, including their physicochemical properties and functional performance, such as bioavailability, stability, and digestibility, which may support promising application of the phenol and polysaccharide complex in health food industry. In this study, two complexes with potential existence in highland barley, such as β-glucan-ferulic acid (GF) and β-glucan-quercetin (GQ), were prepared using the equilibrium dialysis method in vitro. FTIR and SEM results showed that ferulic acid and quercetin formed complexes with β-glucan separately, with covalent and non-covalent bonds and a dense morphological structure. The pH value, reaction temperature, and concentration of phosphate buffer solution (PBS) were confirmed to have an impact on the formation and yield of the complex. Through the test of the response surface, it was found that the optimum conditions for GF and (GQ) preparations were a pH of 6.5 (6), a PBS buffer concentration of 0.08 mol/L (0.3 mol/L), and a temperature of 8 °C (20 °C). Through in vitro assays, GF and GQ were found to possess good antioxidant activity, with a greater scavenging effect of DPPH, ABTS, and hydroxyl radical than the individual phenolic acids and glucans, as well as their physical mixtures. Taking GF as an example, the DPPH radical scavenging capacity ranked as GF (71.74%) > ferulic acid (49.50%) > PGF (44.43%) > β-glucan (43.84%). Similar trends were observed for ABTS radical scavenging (GF: 54.56%; ferulic acid: 44.37%; PGF: 44.95%; β-glucan: 36.42%) and hydroxyl radical elimination (GF: 39.16%; ferulic acid: 33.06%; PGF: 35.51%; β-glucan: 35.47%). In conclusion, the convenient preparation method and excellent antioxidant effect of the phenol–polysaccharide complexes from highland barley provide new opportunities for industrial-scale production, development, and design of healthy food based on these complexes.